Analisis Penyusunan Dan Penyajian Laporan Keuangan Berdasarkan Sak-Etap (Studi Kasus Di Perumdam Tirta Pandalungan Jember) - Alufiah, Wildatul; Halim, Moh; Martiana, Nina (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The research results show that Perumdam Tirta Pandalungan Jember has implemented SAK ETAP in the preparation and presentation of their financial reports. The transaction recording process starts from recording in the general journal based on valid transaction evidence. Each transaction is then posted to the general ledger. The final results of the ledger are summarized in a work sheet, which is then used as the basis for preparing financial reports. Consistent application of SAK ETAP helps ensure that a company's financial reports are prepared in a structured and orderly manner, which in turn supports better and sustainable management decision making. The financial report of Perumdam Tirta Pandalungan Jember for the 2022 financial year has met the provisions stipulated by SAK ETAP. The report includes five main components: balance sheet, income statement, change in equity report, cash flow statement, and Notes to Financial Statements (CALK). The preparation and presentation of these financial reports is carried out in accordance with applicable accounting standards, ensuring that the information presented is relevant, transparent and reliable. This is important not only for the company's internal interests but also for external stakeholders who need accurate information for evaluating company performance and investment decisions. Compliance with SAK ETAP also shows the company's commitment to maintaining transparency and accountability in its financial reporting.